The inorganic pyrophosphatase activity of erythrocytes in favism - Ernişli, Güngör; Brunetti, Faolo (The Turkish Journal of Pediatrics, 1961)
Inorganic pyrophosphatase activity of erythrocytes was found to be decreased in subjects affected by the glucose-6-phosphate dehydrogenase deficiency. During the acute hemolytic episode of favism, pyrophosphatase activity shows a further critical fall. Pyrophosphatase from glucose-6-phosphate dehydrogenase deficient erythrocytes is easily inactivated when RBC are incubated with proper amounts of acetylphenylhydrazine; such instability can be used for the detection of the glucose-6-phosphate dehydrogenase deficiency.